The Estrogenic Content of Rodent Diets, Bedding, Cages, and Water Bottles and Its Effect on Bisphenol A Studies - Thigpen, Julius E (American Association for Laboratory Animal Science, 2013)
The lowest observed adverse effect level for bisphenol A (BPA) in mice and rats is currently poorly defined due to inconsistent study designs and results in published studies. The objectives of the current study were to (1) compare the estrogenic content of rodent diets, bedding, cages, and water bottles to evaluate their impact on the estrogenic activity of BPA and (2) review the literature on BPA to determine the most frequently reported diets, beddings, cages, and water bottles used in animal studies. Our literature review indicated that low-dose BPA animal studies have inconsistent results and that factors contributing to this inconsistency are the uses of high-phytoestrogen diets and the different routes of exposure. In 44% (76 of 172) of all reports, rodents were exposed to BPA via the subcutaneous route. Our literature review further indicated that the type of diet, bedding, caging, and water bottles used in BPA studies were not always reported. Only 37% (64 of 172) of the reports described the diet used. In light of these findings, we recommend the use of a diet containing low levels of phytoestrogen (less than 20 µg/g diet) and metabolizable energy (approximately 3.1 kcal/g diet) and estrogen-free bedding, cages, and water bottles for studies evaluating the estrogenic activity of endocrine-disrupting compounds such as BPA. The oral route of BPA exposure should be used when results are to be extrapolated to humans.